Th-U ages of a stalagmite from the Kleegruben Cave (Table 1), supplementary data to: Spötl, Christoph; Mangini, Augusto (2002): Stalagmite from the Austrian Alps reveals Dansgaard-Oeschger events during istotope stage 3: implications for the absolute chronology of Greenland ice cores. Earth and Planetary Science Letters, 203(1), 507-518 - Spötl, Christoph; Mangini, Augusto (PANGAEA - Data Publisher for Earth & Environmental Science, 2002)
A mass-spectrometric uranium-series dated stalagmite from the Central Alps of Austria provides unprecedented new insights into high-altitude climate change during the peak of isotope stage 3. The stalagmite formed continuously between 57 and 46 kyr before present. A series of 'Hendy tests' demonstrates that the outer parts of the sample show a progressive increase of both stable C and O isotope values. No such covariant increase was detected within the axial zone. This in conjunction with other observations suggests that the continuous stable oxygen isotope profile obtained from the axial zone of the stalagmite largely reflects the unaltered isotopic composition of the cave drip water. The delta18O record shows events of high delta18O values that correlate remarkably with Interstadials 15 (a and b), 14 and 12 identified in the Greenland ice cores. Interstadial 15b started rapidly at 55.6 kyr and lasted ~300 yr only, Interstadial 15a peaked 54.9 kyr ago and was even of shorter duration (~100 yr), and Interstadial 14 commenced 54.2 kyr ago and lasted ~3000 yr. This stalagmite thus represents one of the first terrestrial archives outside the high latitudes which record precisely dated Dansgaard-Oeschger (D/O) events during isotope stage 3. Provided that rapid D/O warmings occurred synchronously in Greenland and the European Alps, the new data provide an independent tool to improve the GRIP and GISP2 chronologies.